Cropping Sequence Influenced Crop Yield, Soil Water Content, Residue Return, and CO2 Efflux in Wheat-Camelina Cropping System - E. Obeng; A. Obour; N. O. Nelson; I. A. Ciampitti; Donghai Wang; E. A. Santos (Kansas Agricultural Experiment Station Research Reports, 2017)
Camelina (Camelina sativaL. Crantz) is a short-seasoned oilseed crop with potential as a fallow replacement crop in dryland wheat (Triticum aestivum) - based cropping systems. Crop rotation management can affect the quality and quantity of crop residue return to the system. In addition, residue has the ability to sequester carbon and can affect plant available water. This study was conducted to investigate the effect of replacing fallow with camelina on crop yield, soil water at wheat planting, soil carbon dioxide (CO2) efflux from treatments, and residue return. Treatments were four rotation schemes, and included wheat-fallow (W-F), wheat-sorghum-fallow (W-S-F), wheat-spring camelina (W-SC), and wheat-sorghum-spring camelina (W-S-SC). Our findings showed an increase in crop residue with increasing cropping intensity. Ground cover in W-S-SC, W-S-F, and W-SC were similar, but greater than that with W-F. Soil CO2efflux in W-SC was greatest among the crop rotations regardless of sampling time. Average CO2efflux in W-SC was 11.3, 26.5, and 7.6 pounds of CO2per acre per hour in the spring, summer, and fall, respectively. Soil water content at 0-24 in. was greater in W-S-F (7.2 in.) compared to W-SC (6.0 in.), and W-S-SC (6.0 in.). However, W-S-F and W-F (6.6 in.) were not different. Wheat and sorghum yields were not affected by crop rotation. However, camelina yields were greater in W-SC (754 lb/a) compared to W-S-SC (339 lb/a) rotation.
Keywords: Camelina; wheat; soil carbon dioxide efflux; soil moisture